Newly Isolated Acidithiobacillus sp. Ksh From Kashen Copper Ore: Peculiarities of EPS and Colloidal Exopolysaccharide - Vardanyan, Narine; Badalyan, Hamlet; Markosyan, Levon; Vardanyan, Arevik; Zhang, Ruiyong; Sand, Wolfgang (Frontiers in Microbiology, 2020)
A novel strain of an iron- and sulfur-oxidizing bacterium was isolated from a natural biotope at Kashen copper ore (Martakert Province, Republic of Artsakh). The strain is able to grow and oxidize ferrous ions in the range of pH 1.4-2.6 with optimal pH 2.0. The optimal temperature for growth is 35 °C. Acidithiobacillus sp. Ksh has shown the highest activity for pyrite oxidation among other strains. It also demonstrated high activity in oxidation for copper and copper-gold bearing ores (Armenia). The isolate Acidithiobacillus sp. Ksh was identified as Acidithiobacillus ferrooxidans based on phylogenetic and physiological studies. Comparative studies of EPS production by cells grown on ferrous ions or pyrite were carried out. The chemical composition of capsular and colloidal EPS produced by Acidithiobacillus (At.) ferrooxidans Ksh were revealed to be proteins and carbohydrates. Exosaccharide produced by At. ferrooxidans Ksh is present mainly as polysaccharide in contrast to Leptospirillum (L.) ferriphilum CC, which is oligosaccharide. The structural difference of colloidal particles of these polysaccharides was due to the degree of hydration of the saccharide molecules.